Freud's British family - Willoughby, Roger, author.
1 online resource.
Keywords: Freud's British Family presents ground-breaking research into the lives of the British branch of the Freud family, their connections to the founder of psychoanalysis, and into Freud's relationship to Britain. Documenting the complex relationships the elder Freud brothers had with their much younger brother Sigmund, Freud's British Family reveals the significant influence these hitherto largely forgotten Freuds had on the mental economy of the founder of psychoanalysis. Roger Willoughby shows how these key family relationships helped shape Freud's thinking, attitudes, and theorising, including emerging ideas on rivalry, the Oedipus complex, character, and art. In addition to considering their correspondence and meetings with Freud in continental Europe, the book carefully documents Freud's own visits to his brothers and to Britain in 1875 and again in 1908. Freud's British Family concludes with a discussion of Freud's final 15 months in London after he left Nazi Vienna as a refugee. Freud's British Family offers a rich, contextualised understanding of the sibling, familial, and socio-cultural ties that went into forming the tapestry of psychoanalysis. Freud's British Family will be of great interest to psychoanalysts and psychotherapists in practice and in training, and to scholars of the history of psychoanalysis, twentieth century history, psychosocial studies, and Jewish studies.